PENGARUH KELEKATAN TERHADAP KESEJAHTERAAN PSIKOLOGIS YANG DIMEDIASI OLEH RESILIENSI PADA REMAJA DENGAN ORANG TUA BERCERAI - Puspitasari, Putri; Maslihah, Sri; Wulandari, Anastasia (Program Studi Psikologi Universitas Pendidikan Indonesia, 2020)
The aim of this study was to examine the correlation of attachment on psychological well-being with resilience act as mediator. Participants were 127 high school adolescents with parent divorced while aged 0 to 12 years old. Attachment was assessed by Inventory of Parent and Peer Attachment (IPPA), resilience was assessed by Resilience Scale (RS), and psychological well-being was assessed by Psychological Well-Being Scale (PWBS) instruments. Causal mediation analyses were used to examine the proposed mediation effects. Result showed that attachment can predict adolescents’ psychological well-being. On other hand, resilience functioned as a mediator on the correlation.